Quality, health system and governance. The argentinean case - Litewka, Sergio G. (Acta Bioethica, 2010)
Argentina had been a fertile ground for reform attempts, focusing in the quality of its health services and subsequently, improving the accessibility and equity to the system. Even though bioethics, as a tool for interdisciplinary reflection, should had been a participant for the foundations of health policies and the impact on its users, it seems that local bioethics had omitted the deleterious consequences created by the lack of governance and corruption on the Argentinean public and social security healthcare systems, choosing instead for focusing in blurry discussions about universal issues related to solidarity and justice, blaming for the failures to the imposition of foreign economical models.